Microencapsulation: The Emerging Role of Microfluidics - Tendulkar, Sameer; K. Ramasubramanian, Melur; C. Opara, Emmanuel (Micro and Nanosystems, 2013)
The technique of microencapsulation was introduced nearly eighty years ago and its potential application in cell therapy was described almost fifty years later. The technique offers a wide range of applications in both industrial products and personalized medicine. The potential application of the technique in pancreatic islet immunoisolation prior to transplantation was first described in 1980 with the resulting construct termed as bioartificial pancreas. Since that first description of microencapsulated islet technology, interest has waxed and waned because of the conflicting data that have been generated in a variety of experimental and clinical studies. Routine clinical application has been impaired because of a number of factors including the need to optimize the technique, determination of the optimum site of transplantation, and the scarcity of appropriate scaled up devices for high throughput fabrication of the construct to be used in large animals and human studies. In this review article, we discuss the microencapsulation procedure and its various applications, and current impediments to routine use of this technology in the biomedical setting especially in encapsulated islet transplantation. In particular, we highlight the role of microfluidics in microencapsulation in many areas of industrial and medical applications. In medical applications, we have highlighted developments in the bioartificial pancreas and the outstanding issues that need to be resolved to make this technology a viable treatment option for individuals afflicted with Type 1 diabetes.
Keywords: Microfluidics